2002
DOI: 10.1289/ehp.02110s5689
|View full text |Cite
|
Sign up to set email alerts
|

Transport of toxic metals by molecular mimicry.

Abstract: Intracellular concentrations of essential metals are normally maintained within a narrow range, whereas the nonessential metals generally lack homeostatic controls. Some of the factors that contribute to metal homeostasis have recently been identified at the molecular level and include proteins that mediate import of essential metals from the extracellular environment, those that regulate delivery to specific intracellular proteins or compartments, and those that mediate metal export from the cell. Some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
151
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(156 citation statements)
references
References 82 publications
1
151
0
3
Order By: Relevance
“…Studies of MeHg transport and accumulation in endothelial cells of the blood-brain barrier and secretion from liver cells (Kerper et al, 1992;Ballatori, 2002) demonstrated that mercury is carried across cell membranes as a complex with small molecular weight endogenous thiol containing molecules. Specifically methyl mercury enters the cells as a complex with the amino acid L-cysteine and exits the cells as a complex with reduced glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of MeHg transport and accumulation in endothelial cells of the blood-brain barrier and secretion from liver cells (Kerper et al, 1992;Ballatori, 2002) demonstrated that mercury is carried across cell membranes as a complex with small molecular weight endogenous thiol containing molecules. Specifically methyl mercury enters the cells as a complex with the amino acid L-cysteine and exits the cells as a complex with reduced glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, no specific, dedicated mechanisms have evolved for their uptake, at least in most animal species. Yet, many studies have proven that these toxic metals do indeed gain entry into various target cells (for reviews, see Clarkson, 1993;Ballatori, 2002;Zalups, 2000a;Zalups and Ahmad, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mimicry refers to the phenomenon whereby the bonding of metal ions to nucleophilic groups on certain biomolecules results in the formation of organo-metal complexes that can behave or serve as a structural and/or functional homolog of other endogenous biomolecules or the molecule to which the metal ion has bonded ( Fig. 1; Ballatori, 2002;Clarkson, 1993;Zalups, 2000a). Ionic mimicry, on the other hand, refers to the ability of an unbound, native, cationic species of a metal to mimic an essential element or cationic form of that element (Clarkson, 1993;Wetterhahn-Jennette, 1981;Zalups and Ahmad, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cd induces oxidative stresses by producing reactive oxygen species (ROS), which cause damage to biological molecules such as lipids, proteins and DNA (Chappie et al, 1997;Dovzhenko et al, 2005). Although zinc (Zn) is an essential element for organisms, excessive Zn can induce potential toxicities such as genotoxicity and immunotoxicity resulting in deleterious effects on fertilization, sexual maturity, and growth of the organisms (Münzinger et al, 1988;Ballatori et al, 2002;Murphy et al, 2011). In fact, improperly treated wastewater has led to severe contamination of Cd and Zn in the Bohai Sea (Zhang, 2001;Mao et al, 2009), which demonstrates the importance of monitoring these metal elements in this habitat.…”
Section: Introductionmentioning
confidence: 99%